Acurácia do teste ergométrico no diagnóstico da reestenose coronariana após angioplastia com implante de Stent convencional em pacientes assintomáticos - Oliveira, Fábio Rezende de Figueiredo (2012)
The detection of in-stent restenosis is important in clinical practice by providing useful information to guide therapy. The objectives of this study were to evaluate the effectiveness of the exercise test (ET) in the detection of restenosis after percutaneous transluminal coronary angioplasty with stent conventional implantation (Stent-ATC) and, as a gold standard, coronary angiography. We studied 25 asymptomatic patients, aged between 44 and 83 years, who underwent PTCA-Stent for at least six months. The patients underwent TE employing the Bruce protocol. The positivity criteria for ischemia was ST segment depression > 1mm, measured at the J point and with horizontal or descending. The results obtained in TE were compared with those of coronary angiography is considered the in-stent restenosis lesions with obstruction > 50%. We estimated the sensitivity and specificity and positive predictive value and negative procedure. Of the individuals studied, 10 (40%) had in-stent restenosis by angiographic criteria, and only 3 (12%) had positive TST tests for ischemia. The relationship between the TE and coronary angiography was not significant (p = 0.315), indicating that the tests are independent. The concordance between the diagnoses was low (Kappa coefficient: 0.151), the same occurring with the sensitivity (20%). The specificity of the test was high (93%) and positive predictive value 65.56% and negative predictive value 63.63%. The overall efficiency of the test is estimated with accuracy low 63.98%. We conclude that the TE has low sensitivity and high specificity in detecting in-stent restenosis in asymptomatic patients. The overall efficiency of ET is low.